Theoretical Dilemmas of the Natural Monopolistic Position of Network Based Public Utilities - Kádár Horváth, Ágnes (Theory, Methodology, Practice – Review of Business and Management, 2011)
The change in the market of public utilities – the liberalisation of markets – is a much debated and highly significant tendency in today’s economy. Many competing, contradicting views have been published on this issue. The demand for the liberalisation of the market of public utilities has become stronger in certain professional circles, emphasising the benefits of the competition evolving as a consequence of the opening of the market. The idea of privatisation was closely linked to liberalisation. According to other schools of thought, market mechanisms are not capable of efficient operation in all cases; public utilities are the state’s responsibility and marketing them has unchangeable negative consequences.